The effect of material properties variation on Ccipper cutter life - Tan, Hui Wen (School of Materials Engineering, University Malaysia Perlis, 2010)
The effect of material properties variation on clipper cutter life onto the cutter that provided by the Covidien Company were evaluated and compared. The material and mechanical properties of the Sample A, Sample B and Sample C were characterized and analyzed using several complementary techniques. Material properties which are the material composition and microstructure of the samples were analyzed by using Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS). Results show that due to the existing of the large amount of element Fe, the samples can be classified as steel. With the present of the 0.9%~1.5% of carbon, the three samples can be also classified as high carbon steel. It shows that the Sample B is the hardest due the highest amount of carbon. The other elements, zinc, aluminium and copper that are observed from the samples increase their hardness, strength and improve the wear resistance. Mechanical properties were measured using Rockwell Hardness test. Result shows that the Sample B, 124.9HB is the hardest among three samples.